Difficulties in surgical management of consecutive exotropia - Broniarczyk-Loba, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Difficulties in surgical management of consecutive exotropia. Consecutive exotropia occurs in formerly esotropic patients without binocular vision, either spontaneously or as a result of surgical overcorrection. However, the above cannot provide sufficient explanation in all cases. Patients with consecutive exotropia mostly complain about aesthetic considerations, although a numerous group of patients reports disturbing diplopia. Patients with consecutive exotropia require particular attention of the surgeons, due to the difficulties in pre-operative assessment and, in turn, in planning thesurgery. The prism adaptation test and botulinum toxin injection used in pre-operative diagnostic assessment often fail to provide the fully reliable information concerning the potential cortical vision suppression, anomalous retinal correspondence and the risk of postoperative diplopia (including paradoxical diplopia). Moreover, many surgeons emphasize the role of technical difficulties experienced during the surgery performed in patients with consecutive exotropia, especially during the reoperation. The preoperative assessment in these patients must include the forced duction test in order to determine which eye should actually be addressed during the surgery. The ocular muscle strength must be balanced during the reoperation, which requires extensive surgical experience and often also the intraoperative adjustment of the primary surgical plan. However, listening patients’ concerns regarding satisfactory aesthetic results and considering the risk of postoperative diplopia still remain of the utmost importance.